Integration of measurable residual disease by WT1 gene expression and flow cytometry identifies pediatric patients with high risk of relapse in acute myeloid leukemia - Ahmed, Sonia; Elsherif, Mariam; Yassin, Dina; Elsharkawy, Nahla; Mohamed, Ayman S.; Yasser, Nouran; Elnashar, Amr; Hafez, Hanafy; Kolb, Edward A.; Elhaddad, Alaa (Frontiers in Oncology, 2024)
Background Molecular testing plays a pivotal role in monitoring measurable residual disease (MRD) in acute myeloid leukemia (AML), aiding in the refinement of risk stratification and treatment guidance. Wilms tumor gene 1 (WT1) is frequently upregulated in pediatric AML and serves as a potential molecular marker for MRD. This study aimed to evaluate WT1 predictive value as an MRD marker and its impact on disease prognosis. Methods Quantification of WT1 expression levels was analyzed using the standardized European Leukemia Network real-time quantitative polymerase chain reaction assay (qRT-PCR) among a cohort of 146 pediatric AML patients. Post-induction I and intensification I, MRD response by WT1 was assessed. Patients achieving a ≥2 log reduction in WT1MRD were categorized as good responders, while those failing to reach this threshold were classified as poor responders. Results At diagnosis, WT1 overexpression was observed in 112 out of 146 (76.7%) patients. Significantly high levels were found in patients with M4- FAB subtype (p=0.018) and core binding fusion transcript (CBF) (RUNX1::RUNX1T1, p=0.018, CBFB::MYH11, p=0.016). Following induction treatment, good responders exhibited a reduced risk of relapse (2-year cumulative incidence of relapse [CIR] 7.9% vs 33.2%, p=0.008). Conversely, poor responders’ post-intensification I showed significantly lower overall survival (OS) (51% vs 93.2%, p<0.001), event-free survival (EFS) (33.3% vs 82.6%, p<0.001), and higher CIR (66.6% vs 10.6%, p<0.001) at 24 months compared to good responders. Even after adjusting for potential confounders, it remained an independent adverse prognostic factor for OS (p=0.04) and EFS (p=0.008). High concordance rates between WT1-based MRD response and molecular MRD were observed in CBF patients. Furthermore, failure to achieve either a 3-log reduction by RT-PCR or a 2-log reduction by WT1 indicated a high risk of relapse. Combining MFC-based and WT1-based MRD results among the intermediate-risk group identified patients with unfavorable prognosis (positive predictive value [PPV] 100%, negative predictive value [NPV] 85%, and accuracy 87.5%). Conclusion WT1MRD response post-intensification I serves as an independent prognostic factor for survival in pediatric AML. Integration of WT1 and MFC-based MRD results enhances the reliability of MRD-based prognostic stratification, particularly in patients lacking specific leukemic markers, thereby influencing treatment strategies.